A Tracking System to Enhance Transportation of Examination Materials based on Spatial and Cloud Technologies - Milumbe, Banji; Phiri, Jackson; Nyirenda, Mayumbo (Zambia ICT Journal, 2021)
This article is an extract of the ongoing study which seeks to develop a framework for secure transportation, tracking and storage of examination question papers, answer scripts using spatial data, sensing, and cloud technologies. This part of the study investigated the transportation of examination materials in relation to examination malpractices and leakages. Based on the findings, the study explored the use of GPS, GPRS/GSM and cloud technologies to enhance the distribution process of examination question papers and answer scripts. We proposed a GPS tracking system which would ensure real-time tracking and monitoring of the examination distribution process. The primary benefit of this system is that the transportation vehicles will always be tracked and remain monitored such that if there is any holdup, immediate action can to be taken. Also since GPS allows constant updates in real-time, any sort of uneven event happening, the main station will be informed immediately. This helps timely action to be taken and also eliminates human interventions or rather depending on humans to report any uneven event. The baseline study indicated that the challenges faced in the distribution process were mainly lack of reliable transportation vehicles which accounted for 67% of those who did not have any designated vehicles. A remote monitoring system was proposed as a way of improving the distribution process.